“Interpersonal Communication for Maintenance Relationship after Divorce” - Siska Nofianti .; Agus Naryoso S,Sos, M.Si (Interaksi Online, 2016)
The frequent phenomena in the society find that there are many ex-couples who have poor communication after divorce. This causes both of couples being awkward in maintaining an effective interaction to one another. Ideally, we shall keep good communication with everyone, including with the ex (boyfriend or girlfriend). It is because we may meet the ex or even need his/her help in the future. Using a qualitative approach, this research has a purpose to describe about “Interpersonal Communication for Relationship Maintenance after Divorce”. Moreover, this research refers to a post-positivistic paradigm with applying a phenomenology method. The subjects of this research are two ex-couples as the main informants. In addition, this research applies mostly about Relational Maintenance Theory since it discusses the ways to maintain good communication with everyone and also with the ex. The result of this research shows that interpersonal communication with the ex will happen if both of them agree to reestablish communication after divorce. This interaction is started by having a motivation to keep in touch and to help one another even when they already became an ex-couple. Also, the ex-couple should still give attention, raise spirit, and be open to each other in order to easily create a friendship among them. Besides verbal communication which is done by texting, calling or using social media, the ex-couple also establishes non-verbal communication by dating. Dating is used to know their intimacy through getting close, having eye contact, having the touch, and showing gestures. The informants of an ex-couple who agreed to divorce will sit side by side, look at each other, and have the touch when they meet again. On the other hand, another ex-couple as the next informants who have a conflict after divorce tend to sit face to face, avoid looking at one another, and have no the touch. Nevertheless, the two ex-couples admit that they are still nervous when they meet again. In short, this research discovers that an initiative to break up a relationship can be decided by the woman or the man.